2013
DOI: 10.1902/jop.2012.120051
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Arterial Disease Associated With Caries and Periodontal Disease

Abstract: There was a positive relationship between periodontitis based on AL and PAD determined by the ABI (odds ratio = 8.18).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 46 publications
3
50
2
1
Order By: Relevance
“…A cross‐sectional analysis of the NHANES population showed that periodontal attachment loss of 3 mm or more was significantly associated with PAD (OR = 2.25, 95% CI: 1.20–4.22; Lu, Parker, & Eaton, ). In a case–control study, periodontal disease defined as clinical attachment loss ≥4 mm in at least 30% of the six measured sites was strongly associated with risk of PAD (OR = 8.18, 95% CI: 1.21–35.23; Soto‐Barreras et al., ). A small case–control study from Japan suggested that periodontitis patients had a fivefold higher risk of developing PAD compared with periodontally healthy controls (OR = 5.45, 95% CI: 1.57–18.89; Chen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A cross‐sectional analysis of the NHANES population showed that periodontal attachment loss of 3 mm or more was significantly associated with PAD (OR = 2.25, 95% CI: 1.20–4.22; Lu, Parker, & Eaton, ). In a case–control study, periodontal disease defined as clinical attachment loss ≥4 mm in at least 30% of the six measured sites was strongly associated with risk of PAD (OR = 8.18, 95% CI: 1.21–35.23; Soto‐Barreras et al., ). A small case–control study from Japan suggested that periodontitis patients had a fivefold higher risk of developing PAD compared with periodontally healthy controls (OR = 5.45, 95% CI: 1.57–18.89; Chen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Dental caries diagnostic criteria were determined in terms of the decayed, missing, and filled teeth (DMFT) index of the World Health Organization. Soto-Barreras et al reported that there were significant differences between the DMFT index (p = 0.0002) and missing teeth (p = 0.0459) in patients with peripheral arterial disease compared with a control group [25]. Kaneko et al reported that root caries is associated with an increased risk for dysrhythmias in a non-smoking elderly population [odds ratio (OR), 5.84; p = 0.04] [24].…”
Section: Discussionmentioning
confidence: 99%
“…Dental caries, as well as periodontitis, has also been reported to be associated with cardiovascular events [22][23][24][25], but the association in Japan has not been studied to date.…”
mentioning
confidence: 99%
“…Edentulism, which was used as a proxy of periodontitis and chronic inflammation, was also investigated in the entire population, as some studies have shown an association between this covariate and PAD [29, 30]. For this, a rural dentist performed an oral exam during the survey with emphasis on the number of remaining teeth.…”
Section: Methodsmentioning
confidence: 99%